Kepentingan Terbaik Anak dalam Hak Waris Anak dari Perkawinan yang Tidak Tercatat: Analisis Normatif SEMA No. 3/2023 - Furziah, Furziah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study examines the legal protection of children born from unregistered marriages in Indonesia, a context where they often face discrimination in inheritance rights despite being normatively linked to their biological fathers. The main problem lies in the limited recognition of their legal status, which undermines the fulfillment of the best interest of the child (BIC) principle as mandated by the Convention on the Rights of the Child. This research aims to analyze the normative framework of Supreme Court Circular Letter (SEMA) No. 3 of 2023 and its role in safeguarding the inheritance rights of children from unregistered marriages. Using a normative juridical method with statutory and conceptual approaches, the study relies on primary legal sources such as SEMA No. 3/2023 and relevant secondary literature. The findings show that SEMA No. 3/2023 represents a progressive legal development through the introduction of wasiat wajibah, which provides children with limited access to inheritance rights in accordance with the BIC principle. However, the protection remains partial, focusing mainly on inheritance while neglecting broader aspects of child welfare such as education, health, and social security. The study concludes that although SEMA No. 3/2023 advances child protection in inheritance matters, further regulatory reinforcement is required to ensure holistic protection for children of unregistered marriages.